Strategic approaches to enhance efficiency and commercial feasibility of copper-based surface plasmon resonance sensing - Anjitha M. Pillai; Niveditha Nair; Mukul K. Das; Sanjay K. Ram (Next Materials)
Despite enormous progress in the field of surface plasmon resonance (SPR) imaging sensor technology in the past three decades, noble metals like Au and Ag, despite their drawbacks, continue to be the metals of choice for plasmonic sensing layers. The conventional architecture of the SPR sensor based on gold/silver and glass prism hinders scaling, portability, and industrial manufacturing. In this contribution, we present a novel architecture of SPR sensor using copper on polycarbonate prism as a cost-effective, scalable, and mass-producible alternative. Various optimization techniques, such as interface layer, protective encapsulation, and 2D affinity layer are explored to address the challenges related to the practical application of copper in a plasmonic sensor. Our results show that optimized architectures of SPR sensor based on copper has a sensitivity of 235.01°/RIU. From a quantitative analysis of the interrelationships among various performance parameters, we have derived a comprehensive sensing parameter that integrates signal quality and sensitivity. The proposed architecture of the copper based SPR sensor can lead to inexpensive, compact, and handy probes that do not sacrifice accuracy or reliability.